Validità e affidabilità delle scale non verbali per l'accertamento del dolore nei pazienti incapaci a fornire autovalutazione - Non-verbal scales validity and reliability for assessment pain in patients unable to self-report - Vincenzo Damico (Publiediting, 2016)
The International Association for the Study of Pain defines pain as an "unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage". A patient's self-report of pain is considered the "gold standard," and clinicians should always attempt to have a patient rate his or her own pain first. According to the findings that emerged from the literature when patients are unable to self-report the use of validated tools are strongly recommended but more studies are needed in the future about the psychometric properties of the scales. This paper comments on a recent systematic review, clinical guidelines and reccomendation about non verbal scale reliability and validity assess pain converserly vital signs or other paramethers.